2022
DOI: 10.3390/cmd3020012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties Decay of Corroded Reinforcement in Concrete—An Overview

Abstract: Among the leading consequences of corrosion in reinforced concrete structures (RCS) the cross section reduction in steel bars should be mentioned, coupled to a decay of their mechanical material properties. This paper recalls the main literature findings on the topic and describes a wide collected database of experimental tensile tests performed on naturally corroded reinforcements. The principal predictive degradation laws available in the scientific literature to assess the residual mechanical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A sensible reduction in the structural capacity of corroded RC elements is observed for corrosion levels higher than 10% in mass loss [24,25]. At this stage, the bond strength can be considered completely loss [14,16], and relevant variations in the reinforcement mechanical properties can be observed in case of pitting corrosion [17]. Moreover, the concrete constitutive law reduces due to the cracking caused by the oxides' expansion [9,10,[26][27][28].…”
Section: Constitutive Laws Of Materials After Corrosion Degradationmentioning
confidence: 99%
See 4 more Smart Citations
“…A sensible reduction in the structural capacity of corroded RC elements is observed for corrosion levels higher than 10% in mass loss [24,25]. At this stage, the bond strength can be considered completely loss [14,16], and relevant variations in the reinforcement mechanical properties can be observed in case of pitting corrosion [17]. Moreover, the concrete constitutive law reduces due to the cracking caused by the oxides' expansion [9,10,[26][27][28].…”
Section: Constitutive Laws Of Materials After Corrosion Degradationmentioning
confidence: 99%
“…In detail, linear relationships relate strength and corrosion level CL, while the ultimate deformation can follow a linear or an exponential trend. A complete review on the degradation laws of corroded reinforcements can be found in [17].…”
Section: The Monotonic Mechanical Properties Of Corroded Steel Reinfo...mentioning
confidence: 99%
See 3 more Smart Citations